High-density monolithic pellets of double-sided graphene fragments based on zeolite-templated carbon. Issue 12 (19th March 2021) - Gabe, Atsushi; Ouzzine, Mohammed; Taylor, Erin E.; Stadie, Nicholas P.; Uchiyama, Naoki; Kanai, Tomomi; Nishina, Yuta; Tanaka, Hideki; Pan, Zheng-Ze; Kyotani, Takashi; Nishihara, Hirotomo
Abstract : High-density and highly porous graphene-based pellets with anomalous gas densification property and glass-like hardness have been fabricated by using zeolite-templated carbon and reduced graphene oxide. Abstract : High-density and highly porous graphene-based pellets that exhibit an anomalous gas densification property have been fabricated by using zeolite-templated carbon (ZTC) as the major component and reduced graphene oxide (rGO) as a pure carbon binder. The unique structure of each ZTC particle consists of double-sided graphene fragments connected in a periodic, three-dimensional framework. The graphene-like sheets of rGO strongly connect the ZTC particles upon hot-pressing via the generation of a large amount of unpaired electron spins, yielding monolithic pellets with exceptional mechanical toughness. The uniaxial pressing applied to the isotropic ordered framework of ZTC during pelletization leads to unique anisotropic structures. The so-obtained pellets represent a high density packing of graphene nanofragments with high volumetric surface area that exhibits high volumetric H2 storage at room temperature.